Global governance in the health sector: changes in the “world order”, in the international arena and impacts in health - Almeida, Celia Maria de (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2020)
This paper examines global governance in the health sector, drawing on discussions of the context in which this term emerged along with other related denominations such as global health, global health governance (or global governance for health), and health diplomacy (or global health diplomacy). It is framed by policy analysis theory, on the assumption that both domestic policies —including foreign policy— and international policies are considered public policies, given that they interrelate different actors, ideas and preferences at the various different stages in the decision-making process: agenda-setting, policymaking, implementation and outcomes. The methodology is qualitative and applies the non-systematic literature review technique.  The far-reaching changes in the world order that became evident in the post-Cold War period (the 1990s) are examined and serve as a reference for the theoretical and conceptual discussion of these terms’ meanings in the new world dynamics in place since then. The study concludes that global governance in the health sector is part of a broader process comprising global governance and its specific variants in a world context of major political, institutional and ideological changes in which the neoliberal perspective is overwhelmingly predominant.  As a result, the term global has itself acquired a particular meaning, embedded in the term global health, which has come to replace international health. The effects of this dynamics on the health sector are seen concretely in the entry of certain health problems as global onto foreign policy agendas and in their utilisation as instruments of geopolitics. Changes to WHO funding and the emergence of new institutional alignments have increased private sector participation in decision-making processes and in health sector regulation, expressed in the privatisation of service provision, cooperation and international aid in health to developing countries, as vertical programmes proliferate and national governments are bypassed to the detriment of public and universal health systems strengthening.